Focal areas of a high rate of fragile X in Indonesia: a long term follow up - Sultana MH Faradz; Tri Indah Winarni (Journal of Biomedicine and Translational Research, 2019)
Fragile X syndrome (FXS) is the most common cause of inherited intellectual disability (ID) and a leading cause of autism spectrum disorder (ASD). FXS is caused by an expansion of CGG repeats >200 in the 5′ untranslated region of the promotor region fragile X mental retardation 1 gene (FMR1), which is located on Xq27.3.  The abnormal CGG expansion leads to methylation and transcriptional silencing of the FMR1 gene, resulting in a reduction or loss of fragile X mental retardation 1 protein (FMRP) and causes long, thin, and immature dendritic spines, which lead to deficits in cognitive function, behavioral problems, and learning ability